Extranodal Nasal-Type T/NK Lymphoma with Primary Oral Manifestation and Fulminant Course: A Case Report - Müller Filho, Flávio José; Locatelli, Isabela de Paiva; Antunes, Paulo Eduardo Hernandes; Lemos, Bruno Denardi; Eugênio, Guilherme Bernardes Rosa; Albuquerque, André Limeira Tenório de (Brazilian Journal of Case Reports, 2026)
Extranodal nasal-type T/NK lymphoma (ENKTCL-NT) is a rare and aggressive non-Hodgkin neoplasm originating from natural killer (NK) cells or, less frequently, cytotoxic T lymphocytes. This subtype shows a high prevalence in Latin American populations and a strong etiological association with the Epstein–Barr virus (EBV). The present study reports the case of a 61-year-old patient with multiple comorbidities who presented with progressive ulcerated lesions in the oral cavity. Initially managed as a common infectious process, the condition proved refractory to treatment, progressing to extensive tissue necrosis and recurrent bleeding. Following multidisciplinary investigation and immunohistochemical review, the diagnosis of ENKTCL-NT was confirmed. Due to the biological aggressiveness of the neoplasm and the patient’s clinical instability, the outcome was fatal before the initiation of specific oncologic therapy. This case underscores the need for deep and repeated biopsies in destructive midline lesions.